Identifikasi Masalah Kesehatan Berdasarkan Faktor yang Berpengaruh pada Kesehatan Pekerja Pabrik Accu - Ikhyana, Firania Kharismatus; Dewi, Lolita Redhy Kusuma; Fahriansyah, Anhas; Ditsi, Errini Sabilla Lilhawa (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2023)
The development of industries that is engaged in battery manufacturing cannot be separated from occupational safety and health problems because the used materials are chemicals. Every day, there are 6000 cases of work accidents which result in fatalities. The chemicals that needed to make batteries can cause poisoning or are allergens for humans. Searches were carried out via Google Scholars, PubMed, Cochrane Library, ResearchGate and Science Direct. There were 46 journals containing health problem based on factors that influence battery factory workers topics. From 46 journals, there were 16 cross-sectional studies, 7 systematic reviews, 10 literature reviews, 8 cohort studies, 1 meta-analysis, and 4 case-control studies. In this study, it was found that health problems among battery factory workers consisted of several health problems based on influencing factors, there are physical factors, chemical factors, biological factors, and ergonomic factors. In these factors, there are risks that can result in occupational diseases. In terms of physical factors, there are problems with noise, radiation, vibration, and electric current. In chemical factors, there are problems with dust, irritants, and gases. Biological factors that play a role in this problem are pollutants. As well as ergonomic factors related to the occurrence of Low Back Pain. Battery factory workers have many health risk problems that they will contract. Health problems in battery factory workers are based on influencing factors consisting of physical factors, chemical factors, biological factors, and ergonomic factors. These factors can result in occupational diseases.